Investigation of the Functional Properties and Spaces of Multipliers for Group $L(p, q)(G)$-Algebras - Duyar, C.; Eryılmaz, İ. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
Let $G$ be a locally compact Abelian group (noncompact and nondiscrete) with Haar measure. Suppose that $1 < p < ∞$ and $1 ≤ q ≤ ∞$. The purpose of the paper is to define temperate Lorentz spaces and study the spaces of multipliers on Lorentz spaces and characterize them as the spaces of multipliers of certain Banach algebras.